PENGEMBANGAN PUDING DENGAN PENAMBAHAN TEPUNG WORTEL(Daucus Carrota L) DAN KUNING TELUR SEBAGAI ALTERNATIF SNACK FOOD SUMBER PRO VITAMIN A - Sepni Asmira; Delzi Ilham; Partini Widiastika (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2021)
Impaired vision and blindness are still a health problem in the world, including in Indonesia. Efforts to maintain eye health can be done by consuming foods that contain lots of vitamin A or provitamin A. Carrots are a source of provitamin A and egg yolks are a source of fat apart from being a source of vitamin A as well. This study aims to determine the effect of adding carrot flour and egg yolk on organoleptic quality and levels of beta-carotene and fat in pudding. This study is an experimental study using a completely randomized design (CRD) consisting of four treatments and two replications. Observations were made subjectively on taste (organoleptic test) with 25 moderately trained panelists and objective observations included testing the levels of beta-carotene with UV-vis spectrophotometry and fat content testing using the Soxhlet method. Based on the results of the organoleptic test, it was found that the best treatment was treatment B (10:10) with four indicators assessed including color, aroma, texture and taste. The laboratory results showed that the highest beta-carotene content was between sample A (control) and sample B (10:10) with the highest average result in sample B of 50.2 and the highest fat content in sample B was 0.169. It is recommended to further researchers to test the acceptability of the product and make more use of local food in research besides being easy to find and having high nutritional value and economic value.